Intermittent versus continuous erlotinib with concomitant modified "XELOX" (q3W) in first‐line treatment of metastatic colorectal cancer. Issue 23 (1st October 2013) - Ma, Brigette B. Y.; Chan, Stephen L.; Ho, Wing M.; Lau, Wilson; Mo, Frankie; Hui, Edwin P.; Chan, Charles; Poon, Annette; Dattatray, Rasalkar D.; Wong, S. C. Cesar; To, Ka F.; King, Ann D.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND This study evaluated the activity of 2 schedules of erlotinib in combination with chemotherapy, and the prognostic significance of serum amphiregulin (AREG) and transforming growth factor alpha (TGFa) in metastatic colorectal cancer. METHODS A total of 60 untreated patients were randomized to a "continuous" (CON; erlotinib 100 mg daily) or an "intermittent" (INT; erlotinib 150 mg on alternate day on day 2 to 14, then 150 mg daily on days 15 to 21) schedule of erlotinib with a modified XELOX (capecitabine plus oxaliplatin) regimen. Serum levels of AREG and TGFa were determined serially. RESULTS Baseline characteristics were similar between the 2 arms. Of the 58 patients evaluated for response, there was a nonsignificant trend toward a slightly higher overall response rate in the INT arm (66.7%) versus the CON arm (56.7%). At a median follow‐up of 2.8 years, the median overall survival was 18.8 months (95% confidence interval = 11.3‐22.9 months) and 20.7 months (95% confidence interval = 12.5‐31 months, P = .19) for the CON and INT arm, respectively. KRAS mutation did not predict drug response. The 2 arms did not differ significantly in toxicity. Baseline serum TGFa was an independent predictor of progression‐free survival, whereas a drop in serum TGFa and AREG levels following 3 to 4 cycles of treatment were associated with shorter progression‐free survival and overall survival, respectively. CONCLUSIONS The intermittent erlotinib schedule was associated with a higher response rate, although this is not statistically significant. Serum TGFa and AREG levels have prognostic significance in erlotinib‐treated patients with colorectal cancer, and further studies are warranted. Cancer 2013;119:4145–4153. © 2013 American Cancer Society.